2012
DOI: 10.1039/c1cc16209h
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective sorption of alcohols in a homochiral metal–organic framework

Abstract: Single-crystal X-ray diffraction study reveals the host-guest interactions between a homochiral metal-organic framework and two enantiomers of a chiral alcohol providing the key driving force for the enantioselective sorption of alcohols in the framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 39 publications
(29 reference statements)
0
71
0
Order By: Relevance
“…Chiral MOF catalysts with uniform active sites for enantioselective reactions have been developed based on functionalized chiral molecular (pre)catalysts [21][22][23][24][25][26][27][28][29][30] . In a handful of latest studies, the resolution of enantiomers (racemic alcohols and sulphoxides) with chiral MOFs via chromatography [31][32][33][34] , crystallization [35][36][37][38][39][40] and membrane 41,42 has been reported, but only few exhibit good chiral separation performance.…”
mentioning
confidence: 99%
“…Chiral MOF catalysts with uniform active sites for enantioselective reactions have been developed based on functionalized chiral molecular (pre)catalysts [21][22][23][24][25][26][27][28][29][30] . In a handful of latest studies, the resolution of enantiomers (racemic alcohols and sulphoxides) with chiral MOFs via chromatography [31][32][33][34] , crystallization [35][36][37][38][39][40] and membrane 41,42 has been reported, but only few exhibit good chiral separation performance.…”
mentioning
confidence: 99%
“…Chiral PCPs have attracted considerable attention because of their potential applications in chiral recognition [9,10,24]. It was demonstrated that chiral recognition of PCPs was attributed to the difference of accessibility of a chiral molecule to the interaction sites between D-and L-isomer by single crystal X-ray diffraction measurement [24].…”
Section: Chiral Recognitionmentioning
confidence: 99%
“…For example, an experimental single-crystal X-ray diffraction study also points to the host-guest interactions between a homochiral MOF and two enantiomers of a chiral alcohol as the key driving force for the enantioselective sorption of alcohols in the chiral framework. [111] Structure -property relations are important for generic insight and design guides for MOF synthesis. Molecular simulations are particularly suitable to 'screen' many materials in a very efficient manner.…”
Section: Molecular Simulation 593mentioning
confidence: 99%